One click away : a campaign on seatbelt safety in Singapore - Woo, Christoper (2019)
This report presents One Click Away, a seatbelt safety campaign aiming to encourage young Singaporeans to wear their seatbelts in the rear seats of Private Hire Vehicles. The campaign was developed by four final-year students from the Wee Kim Wee School of Communication and Information, at Nanyang Technological University, Singapore. One Click Away is targeted at Singaporeans aged 21-35 years old who frequently use Private Hire Vehicles as a mode of transport. Guided by the Integrated Behavioural Model, research was conducted to assess the target audience’s knowledge, attitudes, and intentions toward seatbelt wearing behaviours. The big idea of “Remind, Reveal, and Relate” was developed to emphasize that wearing a seatbelt is a simple action that goes beyond reducing harm to oneself in the event of an accident. Key messages included 1) Wearing your seatbelt protects yourself, 2) You are legally required to wear your seatbelt, and 3) Wearing your seatbelt is the right thing to do. The campaign was a digital-only campaign that was executed from January to March 2019. A series of informative collaterals, a video, and giveaways were run to educate and engage audiences. After an outcome evaluation, it was seen that there was an increase in 1) knowledge of existing laws on seatbelt safety, 2) positive attitudes towards wearing seatbelts in the rear seats, and 3) intentions to wear seatbelts in the rear seats. A discussion on the limitations, recommendations, and sustainability of the campaign are included after. All relevant data and documents are included as appendices.